Laman Blog: Platform Mencanai Pendapat, Memprojeksi Nilai dan Juri Awam Terhadap Kerajaan - Syahruddin Awg. Ahmad; Nik Norma Nik Hassan; Adnan Hussein (Department of Media and Communication Studies, Faculty of Arts and Social Sciences, Universiti Malaya, 2012)
Internet users in this country celebrate the blogs, microblogs and social networking as an ideal platform to present their ideas and opinions to members of the community. A growing number of bloggers and blogs may provide advantages to visitors of the blog to demonstrate their personal or collective opinions. In the meantime, the collective opinions should be embraced by the authorities in order to ensure the public service delivery is on track. Thus, it is the role of the people (blogs visitors) who become eyes and ears of the government in helping the government to deliver an efficient process of public duties and services. It should be made explicit by using constructive feedback on the quality of public services. However, some people may have their own personal intention which is purportedly used to make a prejudgment towards government especially on issues pertaining to its duties. Hence, it should clearly shows on how the Internet especially blogs being used (or misused) by public as a court to put government in a certain position of guilt or not.